Eksperimental Beton Ringan Struktural dengan Inovasi Serat Polypropylene sebagai Pengendali Retak - Purnawirati, I.G.A.; Herlambang, Fajar Surya (Jurnal Teknik, 2025)
This study aims to evaluate the effect of polypropylene fiber addition on the mechanical properties and crack behavior of structural lightweight concrete using local aggregates from Bali. The research was conducted experimentally by preparing cylindrical specimens (Ø150 × 300 mm) and beam specimens (200 × 200 × 2000 mm). Polypropylene fiber was added at 0% and 0.6% by volume of concrete, with superplasticizer SIKA ViscoCrete-3115 N included to maintain workability. The results show that the addition of polypropylene fibers had no significant effect on the concrete density, which remained below 1900 kg/m³, meeting the structural lightweight concrete criteria of ACI 213R-14. The compressive strength of the fiber-reinforced concrete decreased slightly by about 11.4% compared to the control mix, while the splitting tensile strength increased by 7.5% and the flexural strength increased by 9.9%. The maximum crack width decreased from 0.85 mm to 0.55 mm, indicating that the fibers effectively controlled crack propagation and improved ductility. Overall, the incorporation of 0.6% polypropylene fibers enhanced the crack resistance and toughness of structural lightweight concrete without compromising its low density, making it a promising material for lightweight structural elements in multi-story and prestressed concrete applications.